EFEKTIFITAS IKLAN MEDIA BALIHO PT KENCANA MAJU BERSAMA TERHADAP BRAND AWARENESS CABANG SURABAYA - fisa, esterer (Universitas 17 Agustus 1945 Surabaya, 2024)
PT Kencana Maju Bersama chose billboard advertising media to market its products. It is known that the way to promote this product is by advertising through billboards which have been designed with the characteristic red color, boomerang logo, and also the slogan